Fibroblast activation protein-based theranostics in pancreatic cancer - Cheng, Chien-shan; Yang, Pei-wen; Sun, Yun; Song, Shao-li; Chen, Zhen (Frontiers in Oncology, 2022)
Fibroblast activation protein-α (FAP) is a type II transmembrane serine protease with specific endopeptidase activity. Well-known for the selectively expressed in activated stromal fibroblasts of epithelial cancers but not in quiescent fibroblasts, FAP has received substantial research attention as a diagnostic marker and therapeutic target. Pancreatic cancer is characterized by an abundant fibrotic or desmoplastic stroma, leading to rapid progress, therapy resistance, and poor clinical outcome. Numerous studies have revealed that the abundant expression of FAP in cancer cells, circulating tumor cells, stromal cells, and cancer-associated fibroblasts (CAFs) of pancreatic adenocarcinoma have been implicated in various cancer-related signaling pathways, contributing to cancer progression, invasion, migration, metastasis, immunosuppression, and treatment resistance. This article aims to systematically review the research advancement of FAP in pancreatic adenocarcinoma, including as a diagnostic marker, its therapeutic potential, and its correlation with prognosis; illustrate the functional role of FAP-overexpressing stromal cells, especially CAFs, in tumor immuno- and metabolic-microenvironment; summarize the underlying mechanism of FAP-overexpressed CAFs contributing to pancreatic cancer progression and treatment resistance; discuss whether targeting FAP-overexpressed CAFs could be a potential therapeutic strategy; describe the development of FAP-targeted probes in imaging for diagnosis; and finally, explore the emerging basic and clinical studies regarding the bench-to-bedside translation of FAP in pancreatic cancer.